A Short Review: Issues and Threats Pertaining the Security of SCADA Systems - Qassim Q.S.; Jamil N.; Mahdi M.N.; Cob Z.C.; Rahim F.A.; Sidek L.M. (Springer Science and Business Media Deutschland GmbH, 2023)
Authentication; Computer crime; Crime; Cyber attacks; Data privacy; Manufacture; Network security; SCADA systems; Water supply; Control signal; Electricity delivery; Electricity-generation; Manufacturing facility; National infrastructure; SCADA; Security; Sensor signals; Transportation network; Vulnerability; Cryptography